2017
DOI: 10.3390/catal7040101
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Heterometallic (Fe6Na7 and Fe6Na6) Cage Silsesquioxanes in Oxidations with Peroxides

Abstract: Two types of heterometallic (Fe(III),Na) silsesquioxanes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 75 publications
3
17
0
Order By: Relevance
“…Previously, we reported the ability of CLMSs to catalyze the oxidative formation of amides from alcohols . This reaction could be performed using Cu, Fe, or Zn, but the catalyst loading could not be decreased below 1 mol %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported the ability of CLMSs to catalyze the oxidative formation of amides from alcohols . This reaction could be performed using Cu, Fe, or Zn, but the catalyst loading could not be decreased below 1 mol %.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction could be performed using Cu, Fe, or Zn, but the catalyst loading could not be decreased below 1 mol %. With the use of CLMSs, this reaction was efficient with dramatically lower loadings (down to 100 ppm of Cu and 500 ppm of Fe). As 1 and 4 present really atypical structures, their catalytic activity was also evaluated in the transformation of benzylic alcohol into benzamide.…”
Section: Resultsmentioning
confidence: 99%
“…Farnetti investigated iron(II) 2,2’‐ bipyridine complexes in the oxidation of primary and secondary alcohols to provide the corresponding aldehydes and ketones in yields up to 100 % (Table , entry 8) . Shul'pin demonstrated that heterometallic (Fe III ,Na) silsesquioxanes are capable of oxidizing 2‐phenyl ethanol and cyclooctanol to the corresponding ketones in yields up to 92 % utilizing t BuOOH as the oxidant (entry 9) . Mahmudov, da Silva, and Pombeiro synthesized an iron formazan complex to be catalytically active in the solvent‐free, microwave‐assisted oxidation of phenyl ethanol (entry 10) .…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…Specific representatives of cage metallacomplexes, namely cagelike metallasilsesquioxanes (CLMSs), are being intensely studied as (pre)catalysts for numerous chemical processes of high relevance . Cage metallasilsesquioxanes were found to be active in alkene polymerization, epoxidation or epoxide ring opening, metathesis, hydroformylation, Ullmann–Goldberg condensation and amidation . Recently, significant attention was drawn to the potential of CLMS application in the homogeneous oxidation of C–H compounds with activity confirmed for Fe‐,, Cr‐, Ni‐, and Co‐based compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Cage metallasilsesquioxanes were found to be active in alkene polymerization, epoxidation or epoxide ring opening, metathesis, hydroformylation, Ullmann–Goldberg condensation and amidation . Recently, significant attention was drawn to the potential of CLMS application in the homogeneous oxidation of C–H compounds with activity confirmed for Fe‐,, Cr‐, Ni‐, and Co‐based compounds. In turn, the best potential for this type of catalytic activity was found for Cu II ‐based cage silsesquioxanes.…”
Section: Introductionmentioning
confidence: 99%